2019
DOI: 10.1002/chem.201902586
|View full text |Cite
|
Sign up to set email alerts
|

Towards Nonalternant Nanographenes through Self‐Promoted Intramolecular Indenoannulation Cascade by C−F Bond Activation

Abstract: What new scientific questions does this work raise?Every chemist knows that aluminum oxide is quite inert from a chemical viewpoint. Meanwhile, the aromatic CÀFb ond is one of the strongest and thus unreactive bonds in organic chemistry.N evertheless, when mixed together these two allegedly indifferent components become extremely reactive. In our work, we use aluminum oxide to trigger the activation of the CÀFb ond, which in the light of the evidence transforms into an extremely useful functionality.A sw ith A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 39 publications
(58 reference statements)
2
10
0
Order By: Relevance
“…[12,13] However, only the bowl-to-bowl inversion barrier calculated by DFT (B3LYP/6-31G*) was discussed, and no further details,s uch as geometrical parameters or energy levels of frontierm olecular orbitals, were provided (see also the Discussion below). [14] To obtain further insights into the structural details of TIP 2,d ispersion-corrected (D3) [27] DFT methods (B3LYP/6-311G(d,p)) were used to calculate molecular properties. It wasf ound that the input geometry (MM2 optimized models) is crucial to the outcomeo ft he DFT optimization.…”
Section: And Dispersioni Nteractions Of the Bromides With The Aliphatmentioning
confidence: 99%
See 1 more Smart Citation
“…[12,13] However, only the bowl-to-bowl inversion barrier calculated by DFT (B3LYP/6-31G*) was discussed, and no further details,s uch as geometrical parameters or energy levels of frontierm olecular orbitals, were provided (see also the Discussion below). [14] To obtain further insights into the structural details of TIP 2,d ispersion-corrected (D3) [27] DFT methods (B3LYP/6-311G(d,p)) were used to calculate molecular properties. It wasf ound that the input geometry (MM2 optimized models) is crucial to the outcomeo ft he DFT optimization.…”
Section: And Dispersioni Nteractions Of the Bromides With The Aliphatmentioning
confidence: 99%
“…the synthesis of as tructurally relatedt etra-n-octyl TIP by an alumina-mediated HF elimination was reported. [14] Unfortunately,n either full characterization nor detailed discussion on photophysical or electrochemical properties were included. It is known that the Kr egion of pyrene has as ubstantial olefin character,a nd thus the CÀHa ctivation may occur by aH eck coupling mechanism, rather than by aC ÀHa ctivation in which the hydrogen is abstracted from ab enzene ring.…”
mentioning
confidence: 99%
“…Such hydrolysis of C-F bond has already been observed as a side process. 41 Unlike the reported transformation, the current precursor contains two uorine atoms, whereas the polarization of the second C(aryl)-F bond induces the second C-O coupling, this time intramolecular, and subsequent covalent detachment of the product. Some other possible mechanisms occurring via aryne-particles or dehydration were excluded (see ESI †).…”
mentioning
confidence: 83%
“…As a part of our ongoing research on alumina mediated C-F activation, 39,40 we have observed an interesting competition between C(aryl)-C(aryl) coupling and formation of oxygencontaining side products. 41 In certain cases (i.e. when two uorine atoms are dislocated in bay-region) the side products turned out to contain dibenzofuran's moiety.…”
mentioning
confidence: 99%
See 1 more Smart Citation